2017
DOI: 10.1038/s41598-017-02927-2
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept Gene Editing for the Murine Model of Inducible Arginase-1 Deficiency

Abstract: Arginase-1 deficiency in humans is a rare genetic disorder of metabolism resulting from a loss of arginase-1, leading to impaired ureagenesis, hyperargininemia and neurological deficits. Previously, we generated a tamoxifen-inducible arginase-1 deficient mouse model harboring a deletion of Arg1 exons 7 and 8 that leads to similar biochemical defects, along with a wasting phenotype and death within two weeks. Here, we report a strategy utilizing the Clustered, Regularly Interspaced, Short Palindromic Repeats (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…We designed a TALEN pair targeting intron 6 of the Arg1 locus at a region adjacent to the position targeted previously by CRISPR/Cas9. 24 Each monomer contains an array of RVDs to bind the target DNA sequences ( Figure 1 A). The TALEN expression constructs showed good transfection efficiency when introduced into mouse iPSCs by electroporation ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed a TALEN pair targeting intron 6 of the Arg1 locus at a region adjacent to the position targeted previously by CRISPR/Cas9. 24 Each monomer contains an array of RVDs to bind the target DNA sequences ( Figure 1 A). The TALEN expression constructs showed good transfection efficiency when introduced into mouse iPSCs by electroporation ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Surveyor nuclease cleavage to detect NHEJ events of PCR products from the target region produced two bands in the 162- to 186-bp range, with insertion or deletion (indel) frequencies up to 18% in mouse iPSCs ( Figure 1 C), similar to that with CRISPR/Cas9. 24 The TALEN pair target sites were selected to utilize a BspHI restriction site located within the spacer region to determine editing efficiency. The loss of the BspHI recognition sequence was demonstrated by the presence of uncleaved PCR products compared to the control ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This system introduces a plasmid that encodes a desired gene fragment into T cells and then inserts into the cell genome with the transiently expressed transposase enzyme to recognize inverted repeat sequences. A previous genome-wide study indicated that the piggyBac transposon led to stable integration of the transgene and is suitable for clinical application because of the non-preferential integration into proto-oncogenes and reduction of production cost compared with viral vectors 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The iPSC-derived macrophages also expressed substantial amounts of arginase. They believe that their studies provide proof-of-concept for gene editing in UCDs [25].…”
Section: Gene Therapies For Cps1 Deficiencymentioning
confidence: 99%